1998
DOI: 10.1042/bj3310137
|View full text |Cite
|
Sign up to set email alerts
|

Effector-sensitive cross-linking of phosphorylase b kinase by the novel cross-linker 4-phenyl-1,2,4-triazoline-3,5-dione

Abstract: The dienophile 4-phenyl-1,2,4-triazoline-3,5-dione (PTD) was identified as a novel protein cross-linker, and utilized as a conformational probe of phosphorylase b kinase (PhK), a hexadecameric enzyme with the subunit composition (alphabetagammadelta)4. In its reaction with this enzyme, PTD produced five major cross-linked conjugates as resolved by denaturing gel electrophoresis: alphabeta, betagammagamma, alphagamma and a doublet of differently migrating homodimers, betabeta1 and betabeta2. Cross-linking in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
2

Relationship

7
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 37 publications
3
16
0
Order By: Relevance
“…From this it was concluded that, even though ''the activated conformation induced by Ca 2+ shares structural features in common with conformations of PhK induced by other activators, it also has features that are clearly distinct'' (Nadeau et al 1997, 1999). That conclusion is consistent with the results observed using other chemical cross-linkers as conformational probes (Nadeau et al 1997;Ayers et al 1998), with the results herein, and with the fact that, no matter how it is otherwise activated, PhK still requires Ca 2+ for catalytic activity. The deprotonation event(s) leading to a less negative zeta potential (Fig.…”
Section: +supporting
confidence: 82%
“…From this it was concluded that, even though ''the activated conformation induced by Ca 2+ shares structural features in common with conformations of PhK induced by other activators, it also has features that are clearly distinct'' (Nadeau et al 1997, 1999). That conclusion is consistent with the results observed using other chemical cross-linkers as conformational probes (Nadeau et al 1997;Ayers et al 1998), with the results herein, and with the fact that, no matter how it is otherwise activated, PhK still requires Ca 2+ for catalytic activity. The deprotonation event(s) leading to a less negative zeta potential (Fig.…”
Section: +supporting
confidence: 82%
“…It should be noted that assessment of the influence of these serine residues, or their mutants, on β-β interactions as measured in two-hybrid assays may not fully correspond to their role when they are part of the entire PhK complex, in that the remaining α, γ and δ subunits have all been shown to influence the structure of the β subunits. 19,34,38,39 Regardless, the overall results from two-hybrid screens of truncation or mutation constructs of the N terminus of β indicate that this region of the subunit inhibits its self-association and suggest that perturbations in the structure of this region attenuate that inhibition. That Nβ1, but not Nβ2, inhibits PhK A and perturbs crosslinking of β-γ and β-β dimers by GMBS and DFDNB, respectively, suggests that the inhibitory …”
Section: Resultsmentioning
confidence: 89%
“…Using various cross-linkers as structural probes of the hexadecamer, the ␣ subunit forms cross-linked complexes with the catalytic ␥ subunit, and these conjugates are substantially increased upon activation of the enzyme (30,41). One region of ␣ cross-linked to the ␥ subunit has been delineated to lie C-terminal to residue 1015 (41), which overlaps the region containing the second association domain identified herein.…”
Section: Discussionmentioning
confidence: 99%
“…Potential ␣-␣ interactions have not been previously observed with the nonactivated conformer of the PhK holoenzyme. We selected chemical crosslinking at the nonactivating pH of 6.8 as the method to probe for these interactions, because the unambiguous identification of cross-linked conjugates is now possible using PhK subunitspecific mAbs (30). From screening a variety of bifunctional reagents, the heterobifunctional cross-linker sulfo-GMBS was observed to form an ␣-␣ dimer (268.5 kDa, 3.0% error) (Fig.…”
Section: -1237mentioning
confidence: 99%